Anticorrosive flame-retardant polyvinyl chloride composite material and preparation method thereof

Through the synergistic flame retardant combination of porous aluminum hydroxide and red phosphorus and the combination of modified porous aluminum hydroxide and ultrafine aluminum hydroxide, the problems of poor corrosion resistance and insufficient flame retardant in alkaline environments are solved. , achieving efficient flame retardant performance and alkali resistance.

CN119391103APending Publication Date: 2025-02-07CHANGZHOU YONGJIE PLASTIC CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411537951.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Polyvinyl chloride (PVC) materials have poor corrosion resistance in alkaline environments, and their flame retardancy and mechanical properties are affected by high added amounts of aluminum hydroxide fillers.

Method used

Using a synergistic flame retardant combination of porous aluminum hydroxide and red phosphorus, the compatibility and flame retardant properties with PVC are improved by modifying the complexing of porous aluminum hydroxide and ultrafine aluminum hydroxide, and the compatibility and flame retardant properties with PVC are improved, and the chlorosilane solution is passed The modified porous aluminum hydroxide-red phosphorus mixture is wrapped to form a stable and dense carbon layer to improve flame retardant properties.

Benefits of technology

The flame retardant properties and alkali resistance of PVC materials are significantly improved, the amount of aluminum hydroxide is used, and the adverse effects on the mechanical properties and processing properties of the materials are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005112037620000092
    Figure BDA0005112037620000092
  • Figure BDA0005112037620000101
    Figure BDA0005112037620000101
Patent Text Reader

Abstract

The invention provides an anti-corrosion flame-retardant polyvinyl chloride composite material and a preparation method thereof. Comprising the following steps: putting polyvinyl chloride, a composite aluminum hydroxide filler, an acrylate impact modifier, stearic acid, PE wax and dicumyl peroxide into a high-speed stirrer, and uniformly stirring the polyvinyl chloride, the composite aluminum hydroxide filler, the acrylate impact modifier, the stearic acid, the PE wax and the dicumyl peroxide; adding the mixture into a single-screw extruder for extrusion and granulation to obtain granules; and performing injection molding in a micro injection machine to obtain the product. The porous aluminum hydroxide and the red phosphorus have a synergistic flame-retardant effect, the PVC can be thermally degraded to generate chain free radicals during combustion, part of the chain free radicals can be adsorbed by the surface of the porous aluminum hydroxide, and the reaction activity of further combustion pyrolysis of PVC molecules is reduced; small molecular substances formed by thermal decomposition during combustion of red phosphorus have higher capability of capturing chain free radicals than porous aluminum hydroxide, so that the probability of capturing the chain free radicals on the surface of the porous aluminum hydroxide is reduced, the total number of active free radicals in a system is reduced, and the flame-retardant effect on PVC is obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of functional plastic materials, and in particular to an anticorrosive and flame-retardant polyvinyl chloride composite material and a preparation method thereof. Background Art

[0002] Polyvinyl chloride (PVC) is a polymer compound formed by the polymerization reaction of vinyl chloride monomer (VCM). It is a hard plastic in which the C-Cl bond is a dipole, which reduces the movement space between PVC chains, making it hard and brittle. However, it also has excellent physical and chemical properties, water resistance and electrical insulation, mature processing and application technology, and low cost. It is currently a widely used plastic material. It is stable at room temperature, but has poor flame retardancy. At the same time, although polyvinyl chloride (PVC) performs well in certain acidic environments, its corrosion resistance in alkaline environments is relatively poor. Aluminum hydroxide is a common corrosion-resistant flame-retardant filler. It can dehydrate and decompose when heated, absorb a large amount of heat, effectively alleviate the temperature rise and thermal degradation of the polymer, and form a high-temperature resistant dense aluminum oxide protective film on the surface of the polymer to isolate the air and prevent the spread of flames. In addition, aluminum hydroxide releases water vapor when decomposing, which can dilute combustible gases and reduce the combustion rate. However, aluminum hydroxide as a filler also has the following disadvantages: (1) Poor compatibility with PVC: There are structural differences between aluminum hydroxide inorganic fillers and PVC, which leads to weak binding force between them, poor compatibility, and insufficient dispersion in the polymer; (2) Impact on the mechanical properties of PVC: In order to achieve the desired flame retardant effect, the amount of aluminum hydroxide added is often large, which may have an adverse effect on the mechanical properties of the material; (3) Impact on processing performance: A large amount of aluminum hydroxide filler may affect the fluidity and formability of the material. Therefore, aluminum hydroxide must be effectively modified to improve its compatibility with PVC and improve its flame retardancy, thereby reducing its dosage and avoiding affecting its mechanical properties and processing performance. Summary of the invention

[0003] Technical problem to be solved: In view of the above technical problems, the purpose of the present invention is to provide an anti-corrosion and flame-retardant polyvinyl chloride composite material and a preparation method thereof. The porous aluminum hydroxide and red phosphorus have a synergistic flame retardant effect. When PVC burns, it will thermally degrade to produce chain free radicals. Some of the chain free radicals will be adsorbed on the surface of the porous aluminum hydroxide, reducing the reaction activity of the PVC molecules to be further burned and pyrolyzed. When compounded with red phosphorus, the small molecular substances formed by the thermal decomposition of red phosphorus during combustion have a stronger ability to capture chain free radicals than porous aluminum hydroxide, thereby reducing the probability of the porous aluminum hydroxide surface capturing chain free radicals and reducing the total number of active free radicals in the system, thereby significantly improving the flame retardant effect on PVC.

[0004] Technical solution: A corrosion-resistant and flame-retardant polyvinyl chloride composite material, comprising the following components, measured by weight: 100 parts of polyvinyl chloride, 10-15 parts of composite aluminum hydroxide filler, 1 part of acrylic impact modifier, 0.2 parts of stearic acid, 0.3 parts of PE wax, and 6 parts of diisopropylbenzene peroxide. Furthermore, the composite aluminum hydroxide filler is ultrafine aluminum hydroxide and modified porous aluminum hydroxide in a mass ratio of 1:(4-5). The preparation method of the above-mentioned anticorrosive flame-retardant polyvinyl chloride composite material is as follows: S1: Take polyvinyl chloride, composite aluminum hydroxide filler, acrylic impact modifier, stearic acid, PE wax, and dicumyl peroxide, and mix them evenly in a high-speed mixer; S2: adding into a single screw extruder for extrusion granulation to obtain pellets; S3: Place in a micro injection machine and perform injection molding at 145-155°C using a pressure of 10-15MPa to obtain. Furthermore, the preparation method of the modified porous aluminum hydroxide is: Step 1: Mix porous aluminum hydroxide and red phosphorus, pour into an agate ball mill, add agate balls and mix evenly, fill the ball mill with nitrogen, and seal the ball mill; Step 2: The entire system is reacted under an inert gas atmosphere, the speed of the ball mill is set to 450-480 rpm, and the product is collected after ball milling for 40-48 hours; Step 3: The product is dried at 45° C. under vacuum for 12 h to obtain a porous aluminum hydroxide-red phosphorus mixture; Step 4: Add the porous aluminum hydroxide-red phosphorus mixture into the chlorosilane solution, perform ultrasonic treatment for 5-10 minutes, wash with anhydrous ethanol, filter and dry to obtain the product. Furthermore, in step 1, the mass ratio of porous aluminum hydroxide to red phosphorus is 1:(1.8-2.3). Furthermore, in step 1, the ratio of balls to materials is 4:1. Furthermore, in step 4, the chlorosilane solution is prepared by dissolving chlorosilane in ether; the chlorosilane is dimethyldichlorosilane, dimethylchlorosilane and trimethylchlorosilane. Furthermore, the volume ratio of the chlorosilane to the ether is 1:50. Furthermore, the extrusion conditions in S3 are as follows: the set temperatures of the sections in the barrel area are 160°C, 155°C, 155°C, and 165°C, respectively, and the set temperature of the die head is 165°C. Beneficial effects: 1. The present invention effectively wraps the porous aluminum hydroxide-red phosphorus mixture with chlorosilane solution to form a uniform coating on its surface, thereby improving the stability of the porous aluminum hydroxide-red phosphorus, its compatibility with PVC, and its flame retardant performance. 2. The porous aluminum hydroxide and red phosphorus in the present invention have a synergistic flame retardant effect. When PVC burns, it will thermally degrade to produce chain free radicals. Some of the chain free radicals will be adsorbed on the surface of the porous aluminum hydroxide, reducing the reaction activity of the PVC molecules to be further burned and pyrolyzed. When compounded with red phosphorus, the small molecular substances formed by the thermal decomposition of red phosphorus during combustion have a stronger ability to capture chain free radicals than porous aluminum hydroxide, thereby reducing the probability of the porous aluminum hydroxide surface capturing chain free radicals and reducing the total number of active free radicals in the system, thereby significantly improving the flame retardant effect on PVC. 3. The present invention wraps chlorosilane on the surface of the porous aluminum hydroxide-red phosphorus mixture. The red phosphorus will undergo thermal decomposition when heated and can react with oxygen in the surrounding air to generate oxygen-containing phosphoric acid. The oxygen-containing phosphoric acid can promote the endothermic carbonization reaction of PVC, and the chlorosilane can be decomposed into a silicate product containing a Si-O-Si network structure when burned. The Si-O bond energy of the silicate is significantly higher than the CC bond energy of PVC, so it can effectively form a stable and dense carbon layer, thereby effectively isolating the PVC matrix from oxygen and heat, and improving the flame retardant performance. 4. The present invention uses a composite aluminum hydroxide filler, which is a compound of ultrafine aluminum hydroxide and modified porous aluminum hydroxide. The porous structure of porous aluminum hydroxide can provide a larger specific surface area, can adsorb more chain free radicals, and increase the binding force with PVC, while ultrafine aluminum hydroxide can enhance the compatibility and binding force with PVC, thereby improving the processing performance and mechanical properties of the material. Ultrafine aluminum hydroxide has a better flame retardant effect, and the porous structure can load more red phosphorus, and promote dispersion, improve the thermal stability of PVC, and the porous pores can be used as a buffer area for thermal expansion to reduce the damage of thermal stress to PVC. DETAILED DESCRIPTION The present invention proposes an anticorrosive flame retardant polyvinyl chloride composite material and a preparation method thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention will be further described in detail with reference to the following examples. It should be understood that the specific examples described herein are only used to explain the present invention and are not intended to limit the present invention. Example 1 A method for preparing an anticorrosive and flame-retardant polyvinyl chloride composite material, in parts by weight, is as follows: Step 1: Mix porous aluminum hydroxide and red phosphorus in a mass ratio of 1:1.8, pour into an agate ball mill, add agate balls and mix evenly, the ball-to-material ratio is 4:1, fill the ball mill with nitrogen, and seal the ball mill; Step 2: The entire system was reacted under an inert gas atmosphere, the speed of the ball mill was set to 470 rpm, and the product was collected after ball milling for 45 h; Step 3: The product is dried at 45° C. under vacuum for 12 h to obtain a porous aluminum hydroxide-red phosphorus mixture; Step 4: dissolving dimethyldichlorosilane in diethyl ether, wherein the volume ratio of dimethyldichlorosilane to diethyl ether is 1:50, to obtain a chlorosilane solution; Step 5: adding the porous aluminum hydroxide-red phosphorus mixture to the chlorosilane solution, ultrasonically treating for 10 minutes, washing with anhydrous ethanol, filtering and drying, to obtain modified porous aluminum hydroxide; Step 6: Take 100 parts of polyvinyl chloride, 13 parts of composite aluminum hydroxide filler, 1 part of acrylic impact modifier, 0.2 parts of stearic acid, 0.3 parts of PE wax, and 6 parts of dicumyl peroxide, and stir them evenly in a high-speed mixer; the composite aluminum hydroxide filler is ultrafine aluminum hydroxide and modified porous aluminum hydroxide in a mass ratio of 1:4.5; Step 7: adding the extruder to a single screw extruder for extrusion granulation, the extrusion conditions are: the set temperatures of each section of the barrel area are 160° C., 155° C., 155° C., and 165° C., respectively, and the die head set temperature is 165° C. to obtain pellets; Step 8: Place the product in a micro injection machine and perform injection molding at 150°C using a pressure of 13 MPa to obtain the product. Example 2 A method for preparing an anticorrosive and flame-retardant polyvinyl chloride composite material, in parts by weight, is as follows: Step 1: Mix porous aluminum hydroxide and red phosphorus in a mass ratio of 1:2.0, pour into an agate ball mill, add agate balls and mix evenly, the ball-to-material ratio is 4:1, fill the ball mill with nitrogen, and seal the ball mill; Step 2: The entire system was reacted under an inert gas atmosphere, the speed of the ball mill was set to 470 rpm, and the product was collected after ball milling for 45 h; Step 3: The product is dried at 45° C. under vacuum for 12 h to obtain a porous aluminum hydroxide-red phosphorus mixture; Step 4: dissolving dimethyldichlorosilane in diethyl ether, wherein the volume ratio of dimethyldichlorosilane to diethyl ether is 1:50, to obtain a chlorosilane solution; Step 5: adding the porous aluminum hydroxide-red phosphorus mixture to the chlorosilane solution, ultrasonically treating for 10 minutes, washing with anhydrous ethanol, filtering and drying, to obtain modified porous aluminum hydroxide; Step 6: Take 100 parts of polyvinyl chloride, 13 parts of composite aluminum hydroxide filler, 1 part of acrylic impact modifier, 0.2 parts of stearic acid, 0.3 parts of PE wax, and 6 parts of dicumyl peroxide, and stir them evenly in a high-speed mixer; the composite aluminum hydroxide filler is ultrafine aluminum hydroxide and modified porous aluminum hydroxide in a mass ratio of 1:4.5; Step 7: adding the extruder to a single screw extruder for extrusion granulation, the extrusion conditions are: the set temperatures of each section of the barrel area are 160° C., 155° C., 155° C., and 165° C., respectively, and the die head set temperature is 165° C. to obtain pellets; Step 8: Place the product in a micro injection machine and perform injection molding at 150° C. using a pressure of 13 MPa to obtain the product. Example 3 A method for preparing an anticorrosive and flame-retardant polyvinyl chloride composite material, in parts by weight, is as follows: Step 1: Mix porous aluminum hydroxide and red phosphorus in a mass ratio of 1:2.3, pour into an agate ball mill, add agate balls and mix evenly, the ball-to-material ratio is 4:1, fill the ball mill with nitrogen, and seal the ball mill; Step 2: The entire system was reacted under an inert gas atmosphere, the speed of the ball mill was set to 470 rpm, and the product was collected after ball milling for 45 h; Step 3: The product is dried at 45° C. under vacuum for 12 h to obtain a porous aluminum hydroxide-red phosphorus mixture; Step 4: dissolving dimethyldichlorosilane in diethyl ether, wherein the volume ratio of dimethyldichlorosilane to diethyl ether is 1:50, to obtain a chlorosilane solution; Step 5: adding the porous aluminum hydroxide-red phosphorus mixture to the chlorosilane solution, ultrasonically treating for 10 minutes, washing with anhydrous ethanol, filtering and drying, to obtain modified porous aluminum hydroxide; Step 6: Take 100 parts of polyvinyl chloride, 13 parts of composite aluminum hydroxide filler, 1 part of acrylic impact modifier, 0.2 parts of stearic acid, 0.3 parts of PE wax, and 6 parts of dicumyl peroxide, and stir them evenly in a high-speed mixer; the composite aluminum hydroxide filler is ultrafine aluminum hydroxide and modified porous aluminum hydroxide in a mass ratio of 1:4.5; Step 7: adding the extruder to a single screw extruder for extrusion granulation, the extrusion conditions are: the set temperatures of each section of the barrel area are 160° C., 155° C., 155° C., and 165° C., respectively, and the die head set temperature is 165° C. to obtain pellets; Step 8: Place the product in a micro injection machine and perform injection molding at 150°C using a pressure of 13 MPa to obtain the product. Example 4 A method for preparing an anticorrosive and flame-retardant polyvinyl chloride composite material, in parts by weight, is as follows: Step 1: Mix porous aluminum hydroxide and red phosphorus in a mass ratio of 1:2.0, pour into an agate ball mill, add agate balls and mix evenly, the ball-to-material ratio is 4:1, fill the ball mill with nitrogen, and seal the ball mill; Step 2: The entire system was reacted under an inert gas atmosphere, the speed of the ball mill was set to 450 rpm, and the product was collected after ball milling for 48 h; Step 3: The product is dried at 45° C. under vacuum for 12 h to obtain a porous aluminum hydroxide-red phosphorus mixture; Step 4: dissolving dimethyldichlorosilane in diethyl ether, wherein the volume ratio of dimethyldichlorosilane to diethyl ether is 1:50, to obtain a chlorosilane solution; Step 5: adding the porous aluminum hydroxide-red phosphorus mixture to the chlorosilane solution, ultrasonically treating for 10 minutes, washing with anhydrous ethanol, filtering and drying, to obtain modified porous aluminum hydroxide; Step 6: Take 100 parts of polyvinyl chloride, 13 parts of composite aluminum hydroxide filler, 1 part of acrylic impact modifier, 0.2 parts of stearic acid, 0.3 parts of PE wax, and 6 parts of dicumyl peroxide, and stir them evenly in a high-speed mixer; the composite aluminum hydroxide filler is ultrafine aluminum hydroxide and modified porous aluminum hydroxide in a mass ratio of 1:4.5; Step 7: adding the extruder to a single screw extruder for extrusion granulation, the extrusion conditions are: the set temperatures of each section of the barrel area are 160° C., 155° C., 155° C., and 165° C., respectively, and the die head set temperature is 165° C. to obtain pellets; Step 8: Place the product in a micro injection machine and perform injection molding at 150°C using a pressure of 13 MPa to obtain the product. Example 5 A method for preparing an anticorrosive and flame-retardant polyvinyl chloride composite material, in parts by weight, is as follows: Step 1: Mix porous aluminum hydroxide and red phosphorus in a mass ratio of 1:2.0, pour into an agate ball mill, add agate balls and mix evenly, the ball-to-material ratio is 4:1, fill the ball mill with nitrogen, and seal the ball mill; Step 2: The entire system was reacted under an inert gas atmosphere, the speed of the ball mill was set to 480 rpm, and the product was collected after ball milling for 40 h; Step 3: The product is dried at 45° C. under vacuum for 12 h to obtain a porous aluminum hydroxide-red phosphorus mixture; Step 4: dissolving dimethyldichlorosilane in diethyl ether, wherein the volume ratio of dimethyldichlorosilane to diethyl ether is 1:50, to obtain a chlorosilane solution; Step 5: adding the porous aluminum hydroxide-red phosphorus mixture to the chlorosilane solution, ultrasonically treating for 10 minutes, washing with anhydrous ethanol, filtering and drying, to obtain modified porous aluminum hydroxide; Step 6: Take 100 parts of polyvinyl chloride, 13 parts of composite aluminum hydroxide filler, 1 part of acrylic impact modifier, 0.2 parts of stearic acid, 0.3 parts of PE wax, and 6 parts of dicumyl peroxide, and stir them evenly in a high-speed mixer; the composite aluminum hydroxide filler is ultrafine aluminum hydroxide and modified porous aluminum hydroxide in a mass ratio of 1:4.5; Step 7: adding the extruder to a single screw extruder for extrusion granulation, the extrusion conditions are: the set temperatures of each section of the barrel area are 160° C., 155° C., 155° C., and 165° C., respectively, and the die head set temperature is 165° C. to obtain pellets; Step 8: Place the product in a micro injection machine and perform injection molding at 150°C using a pressure of 13 MPa to obtain the product. Example 6 A method for preparing an anticorrosive and flame-retardant polyvinyl chloride composite material, in parts by weight, is as follows: Step 1: Mix porous aluminum hydroxide and red phosphorus in a mass ratio of 1:2.0, pour into an agate ball mill, add agate balls and mix evenly, the ball-to-material ratio is 4:1, fill the ball mill with nitrogen, and seal the ball mill; Step 2: The entire system was reacted under an inert gas atmosphere, the speed of the ball mill was set to 470 rpm, and the product was collected after ball milling for 45 h; Step 3: The product is dried at 45° C. under vacuum for 12 h to obtain a porous aluminum hydroxide-red phosphorus mixture; Step 4: dissolving dimethyldichlorosilane in diethyl ether, wherein the volume ratio of dimethyldichlorosilane to diethyl ether is 1:50, to obtain a chlorosilane solution; Step 5: adding the porous aluminum hydroxide-red phosphorus mixture to the chlorosilane solution, ultrasonically treating for 10 minutes, washing with anhydrous ethanol, filtering and drying, to obtain modified porous aluminum hydroxide; Step 6: Take 100 parts of polyvinyl chloride, 10 parts of composite aluminum hydroxide filler, 1 part of acrylic impact modifier, 0.2 parts of stearic acid, 0.3 parts of PE wax, and 6 parts of diisopropylbenzene peroxide, and stir them evenly in a high-speed mixer; the composite aluminum hydroxide filler is ultrafine aluminum hydroxide and modified porous aluminum hydroxide in a mass ratio of 1:4.5; Step 7: adding the extruder to a single screw extruder for extrusion granulation, the extrusion conditions are: the set temperatures of each section of the barrel area are 160° C., 155° C., 155° C., and 165° C., respectively, and the die head set temperature is 165° C. to obtain pellets; Step 8: Place the product in a micro injection machine and perform injection molding at 150°C using a pressure of 13 MPa to obtain the product. Example 7 A method for preparing an anticorrosive and flame-retardant polyvinyl chloride composite material, in parts by weight, is as follows: Step 1: Mix porous aluminum hydroxide and red phosphorus in a mass ratio of 1:2.0, pour into an agate ball mill, add agate balls and mix evenly, the ball-to-material ratio is 4:1, fill the ball mill with nitrogen, and seal the ball mill; Step 2: The entire system was reacted under an inert gas atmosphere, the speed of the ball mill was set to 470 rpm, and the product was collected after ball milling for 45 h; Step 3: The product is dried at 45° C. under vacuum for 12 h to obtain a porous aluminum hydroxide-red phosphorus mixture; Step 4: dissolving dimethyldichlorosilane in diethyl ether, wherein the volume ratio of dimethyldichlorosilane to diethyl ether is 1:50, to obtain a chlorosilane solution; Step 5: adding the porous aluminum hydroxide-red phosphorus mixture to the chlorosilane solution, ultrasonically treating for 10 minutes, washing with anhydrous ethanol, filtering and drying, to obtain modified porous aluminum hydroxide; Step 6: Take 100 parts of polyvinyl chloride, 15 parts of composite aluminum hydroxide filler, 1 part of acrylic impact modifier, 0.2 parts of stearic acid, 0.3 parts of PE wax, and 6 parts of diisopropylbenzene peroxide, and stir them evenly in a high-speed mixer; the composite aluminum hydroxide filler is ultrafine aluminum hydroxide and modified porous aluminum hydroxide in a mass ratio of 1:4.5; Step 7: adding the extruder to a single screw extruder for extrusion granulation, the extrusion conditions are: the set temperatures of each section of the barrel area are 160° C., 155° C., 155° C., and 165° C., respectively, and the die head set temperature is 165° C. to obtain pellets; Step 8: Place the product in a micro injection machine and perform injection molding at 150°C using a pressure of 13 MPa to obtain the product. Example 8 A method for preparing an anticorrosive and flame-retardant polyvinyl chloride composite material, in parts by weight, is as follows: Step 1: Mix porous aluminum hydroxide and red phosphorus in a mass ratio of 1:2.0, pour into an agate ball mill, add agate balls and mix evenly, the ball-to-material ratio is 4:1, fill the ball mill with nitrogen, and seal the ball mill; Step 2: The entire system was reacted under an inert gas atmosphere, the speed of the ball mill was set to 470 rpm, and the product was collected after ball milling for 45 h; Step 3: The product is dried at 45° C. under vacuum for 12 h to obtain a porous aluminum hydroxide-red phosphorus mixture; Step 4: dissolving dimethyldichlorosilane in diethyl ether, wherein the volume ratio of dimethyldichlorosilane to diethyl ether is 1:50, to obtain a chlorosilane solution; Step 5: adding the porous aluminum hydroxide-red phosphorus mixture to the chlorosilane solution, ultrasonically treating for 10 minutes, washing with anhydrous ethanol, filtering and drying, to obtain modified porous aluminum hydroxide; Step 6: Take 100 parts of polyvinyl chloride, 13 parts of composite aluminum hydroxide filler, 1 part of acrylic impact modifier, 0.2 parts of stearic acid, 0.3 parts of PE wax, and 6 parts of diisopropylbenzene peroxide, and stir them evenly in a high-speed mixer; the composite aluminum hydroxide filler is ultrafine aluminum hydroxide and modified porous aluminum hydroxide in a mass ratio of 1:4; Step 7: adding the extruder to a single screw extruder for extrusion granulation, the extrusion conditions are: the set temperatures of each section of the barrel area are 160° C., 155° C., 155° C., and 165° C., respectively, and the die head set temperature is 165° C. to obtain pellets; Step 8: Place the product in a micro injection machine and perform injection molding at 150°C using a pressure of 13 MPa to obtain the product. Example 9 A method for preparing an anticorrosive and flame-retardant polyvinyl chloride composite material, in parts by weight, is as follows: Step 1: Mix porous aluminum hydroxide and red phosphorus in a mass ratio of 1:2.0, pour into an agate ball mill, add agate balls and mix evenly, the ball-to-material ratio is 4:1, fill the ball mill with nitrogen, and seal the ball mill; Step 2: The entire system was reacted under an inert gas atmosphere, the speed of the ball mill was set to 470 rpm, and the product was collected after ball milling for 45 h; Step 3: The product is dried at 45° C. under vacuum for 12 h to obtain a porous aluminum hydroxide-red phosphorus mixture; Step 4: dissolving dimethyldichlorosilane in diethyl ether, wherein the volume ratio of dimethyldichlorosilane to diethyl ether is 1:50, to obtain a chlorosilane solution; Step 5: adding the porous aluminum hydroxide-red phosphorus mixture to the chlorosilane solution, ultrasonically treating for 10 minutes, washing with anhydrous ethanol, filtering and drying, to obtain modified porous aluminum hydroxide; Step 6: Take 100 parts of polyvinyl chloride, 13 parts of composite aluminum hydroxide filler, 1 part of acrylic impact modifier, 0.2 parts of stearic acid, 0.3 parts of PE wax, and 6 parts of diisopropylbenzene peroxide, and stir them evenly in a high-speed mixer; the composite aluminum hydroxide filler is ultrafine aluminum hydroxide and modified porous aluminum hydroxide in a mass ratio of 1:5; Step 7: adding the extruder to a single screw extruder for extrusion granulation, the extrusion conditions are: the set temperatures of each section of the barrel area are 160° C., 155° C., 155° C., and 165° C., respectively, and the die head set temperature is 165° C. to obtain pellets; Step 8: Place the product in a micro injection machine and perform injection molding at 150°C using a pressure of 13 MPa to obtain the product. Comparative Example 1 The difference between this comparative example and Example 2 is that porous aluminum hydroxide is directly added without modification, as follows: A method for preparing an anticorrosive and flame-retardant polyvinyl chloride composite material, in parts by weight, is as follows: Step 1: Take 100 parts of polyvinyl chloride, 13 parts of composite aluminum hydroxide filler, 1 part of acrylic impact modifier, 0.2 parts of stearic acid, 0.3 parts of PE wax, and 6 parts of dicumyl peroxide, and stir them evenly in a high-speed mixer; the composite aluminum hydroxide filler is ultrafine aluminum hydroxide and porous aluminum hydroxide in a mass ratio of 1:4.5; Step 2: adding the extruder into a single screw extruder for extrusion granulation, the extrusion conditions are: the set temperatures of each section of the barrel area are 160°C, 155°C, 155°C, and 165°C respectively, and the die head set temperature is 165°C to obtain pellets; Step 3: Place in a micro injection machine and perform injection molding at 150°C using a pressure of 13 MPa to obtain. Comparative Example 2 The difference between this comparative example and Example 2 is that ultrafine aluminum hydroxide is not used, and the details are as follows: A method for preparing an anticorrosive and flame-retardant polyvinyl chloride composite material, in parts by weight, is as follows: Step 1: Mix porous aluminum hydroxide and red phosphorus in a mass ratio of 1:2.0, pour into an agate ball mill, add agate balls and mix evenly, the ball-to-material ratio is 4:1, fill the ball mill with nitrogen, and seal the ball mill; Step 2: The entire system was reacted under an inert gas atmosphere, the speed of the ball mill was set to 470 rpm, and the product was collected after ball milling for 45 h; Step 3: The product is dried at 45° C. under vacuum for 12 h to obtain a porous aluminum hydroxide-red phosphorus mixture; Step 4: dissolving dimethyldichlorosilane in diethyl ether, wherein the volume ratio of dimethyldichlorosilane to diethyl ether is 1:50, to obtain a chlorosilane solution; Step 5: adding the porous aluminum hydroxide-red phosphorus mixture to the chlorosilane solution, ultrasonically treating for 10 minutes, washing with anhydrous ethanol, filtering and drying, to obtain modified porous aluminum hydroxide; Step 6: Take 100 parts of polyvinyl chloride, 13 parts of modified porous aluminum hydroxide filler, 1 part of acrylic impact modifier, 0.2 parts of stearic acid, 0.3 parts of PE wax, and 6 parts of diisopropylbenzene peroxide, and mix them evenly in a high-speed mixer; Step 7: adding the extruder to a single screw extruder for extrusion granulation, the extrusion conditions are: the set temperatures of each section of the barrel area are 160° C., 155° C., 155° C., and 165° C., respectively, and the die head set temperature is 165° C. to obtain pellets; Step 8: Place the product in a micro injection machine and perform injection molding at 150°C using a pressure of 13 MPa to obtain the product. Limiting oxygen index test: sample size 130mm×6×3mm, tested according to ASTMD2863 standard; Vertical combustion test: The sample size is 125mm×13mm×3mm, and the nozzle of the blowtorch is kept 10mm away from the sample. After applying an open flame to the sample for 10s, the blowtorch is immediately removed and the burning behavior of the sample is observed. Finally, the results are analyzed according to the UL-94 grade standard; Mechanical properties test: tensile strength is tested according to GB / T1040.1-2018, with a tensile rate of 100 mm / min; Alkali resistance test: refer to the national standard GB / T11547-2008, put the anticorrosive flame retardant polyvinyl chloride composite material in an oven, take it out and weigh it after 24 hours, record the mass as m1, then put it in a NaOH solution with a mass concentration of 40%, keep the temperature at 70℃ for 16 hours, take it out, rinse the surface with deionized water, and then use filter paper to absorb the surface moisture, dry it, weigh it, and record the mass as membrane m2. The weight loss rate is calculated as follows: The results are shown in Table 1 below: Table 1

Claims

1. A corrosion-resistant and flame-retardant polyvinyl chloride composite material, characterized in that: The invention comprises the following ingredients in parts by weight: 100 parts of polyvinyl chloride, 10-15 parts of composite aluminum hydroxide filler, 1 part of acrylic ester impact modifier, 0.2 parts of stearic acid, 0.3 parts of PE wax and 6 parts of diisopropylbenzene peroxide.

2. The anticorrosive flame-retardant polyvinyl chloride composite material according to claim 1, characterized in that: The composite aluminum hydroxide filler is ultrafine aluminum hydroxide and modified porous aluminum hydroxide in a mass ratio of 1:(4-5).

3. The method for preparing the anticorrosive and flame-retardant polyvinyl chloride composite material according to claim 1, characterized in that: The preparation method is as follows: S1: Take polyvinyl chloride, composite aluminum hydroxide filler, acrylic impact modifier, stearic acid, PE wax, and dicumyl peroxide, and mix them evenly in a high-speed mixer; S2: adding into a single screw extruder for extrusion granulation to obtain pellets; S3: Place in a micro injection machine and perform injection molding at 145-155°C using a pressure of 10-15MPa to obtain.

4. The anticorrosive and flame-retardant polyvinyl chloride composite material according to claim 2, characterized in that: The preparation method of the modified porous aluminum hydroxide is: Step 1: Mix porous aluminum hydroxide and red phosphorus, pour into an agate ball mill, add agate balls and mix evenly, fill the ball mill with nitrogen, and seal the ball mill; Step 2: The entire system is reacted under an inert gas atmosphere, the speed of the ball mill is set to 450-480 rpm, and the product is collected after ball milling for 40-48 hours; Step 3: The product is dried at 45° C. under vacuum for 12 h to obtain a porous aluminum hydroxide-red phosphorus mixture; Step 4: Add the porous aluminum hydroxide-red phosphorus mixture into the chlorosilane solution, perform ultrasonic treatment for 5-10 minutes, wash with anhydrous ethanol, filter and dry to obtain the product.

5. The method for preparing the anticorrosive and flame-retardant polyvinyl chloride composite material according to claim 4, characterized in that: In the step 1, the mass ratio of porous aluminum hydroxide to red phosphorus is 1:(1.8-2.3).

6. The method for preparing the anticorrosive and flame-retardant polyvinyl chloride composite material according to claim 4, characterized in that: In step 1, the ratio of balls to materials is 4:

1.

7. The method for preparing the anticorrosive and flame-retardant polyvinyl chloride composite material according to claim 4, characterized in that: The chlorosilane solution in step 4 is prepared by dissolving chlorosilane in ether; the chlorosilane is dimethyldichlorosilane, dimethylchlorosilane and trimethylchlorosilane.

8. The method for preparing the anticorrosive and flame-retardant polyvinyl chloride composite material according to claim 7, characterized in that: The volume ratio of the chlorosilane to the ether is 1:

50.

9. The method for preparing the anticorrosive and flame-retardant polyvinyl chloride composite material according to claim 3, characterized in that: The extrusion conditions in S3 are as follows: the set temperatures of the sections in the barrel area are 160°C, 155°C, 155°C, and 165°C, respectively, and the set temperature of the die head is 165°C.